Rural Early Childhood Education and the intersections of coloniality in the cultural context: an analysis of academic productions - Louriete Ribeiro de Araújo; Samuel Penteado Urban; Arilene Maria Soares de Medeiros (Revista Brasileira de Educação do Campo)
Rural Education is the right of everyone who lives in the countryside, and its historical and social peculiarities must be considered in its provision. However, studies have shown a distancing between schools and their people when these institutions follow the pace, strategies, and time of city's schools. This is a reality that has direct consequences for rural children in their social and cultural practices.Through the analysis of academic productions, more precisely the construction of the state of knowledge, the objective is to identify how research on rural early childhood education has been approached. The search sources start with the Brazilian Digital Library of Theses and Dissertations (BDTD) and the Catalog of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel (CAPES), with the descriptors “Childhoods of the Countryside” AND “Effects of Coloniality” and “Decoloniality”. There is notable concern about the difficulties that persist in rural schools, especially in relation to infrastructure and teacher training. When not closed, they tend to survive with what is left of urban centers, despising the rural school community.